2015
DOI: 10.1161/atvbaha.115.305896
|View full text |Cite
|
Sign up to set email alerts
|

Senescent Vascular Smooth Muscle Cells Drive Inflammation Through an Interleukin-1α–Dependent Senescence-Associated Secretory Phenotype

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
174
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(185 citation statements)
references
References 41 publications
4
174
0
Order By: Relevance
“…The increase in IL-1β is in accord with a previous observation by our group showing increased aortic IL-1β concentrations in with age in mice [10]. IL-10 is an anti-inflammatory cytokine and mice deficient in IL-10 develop arterial dysfunction at a younger age than wild type controls [39]. This suggests that the age-related increase in IL-10 may be a compensatory response in attempt to preserve arterial function with age.…”
Section: Discussionsupporting
confidence: 89%
“…The increase in IL-1β is in accord with a previous observation by our group showing increased aortic IL-1β concentrations in with age in mice [10]. IL-10 is an anti-inflammatory cytokine and mice deficient in IL-10 develop arterial dysfunction at a younger age than wild type controls [39]. This suggests that the age-related increase in IL-10 may be a compensatory response in attempt to preserve arterial function with age.…”
Section: Discussionsupporting
confidence: 89%
“…71 Interestingly, another ATVB publication by Gardner, et al suggested that senescent VSMCs may be active participants in CVD processes and assume a pro-inflammatory state and secrete factors that promote chemotaxis of mononuclear cells in vitro and in vivo and that release active MMP-9, secrete less collagen, and prime endothelial cells and VSMCs to a pro-inflammatory state. 72 And while this was established in a model of atherosclerosis, whether this VSMC phenotype plays a direct role in arterial stiffness remains to be investigated.…”
Section: Underlying Mechanisms Of Arterial Stiffeningmentioning
confidence: 99%
“…97 Moreover, a recent study displayed that senescent human VSMCs develop a proinflammatory state known as SASP. 98 These results suggest that inflammation associated with the normal aging process contributes to the onset of age-related diseases. Ang II stimulation is one of the factors responsible for the cellular senescence of the vasculature.…”
Section: Aging In the Vasculaturementioning
confidence: 89%